The Hobbit : or, There and back again - Tolkien, J. R. R. 1892-1973 (Ballantine Books, 1982)
The adventures of the well-to-do hobbit, Bilbo Baggins, who lived happily in his comfortable home until a wandering wizard granted his wish.